The Effect of Cryptocurrency Returns Volatility on Stock Prices and Exchange Rate Returns Volatility in Nigeria: Array - Jimoh, Sodiq Olaiwola; Oluwasegun, Olawale Benjamin (Acta Universitatis Danubius. Œconomica, 2020)
The global usage and acceptability of bitcoin and other forms of cryptocurrencies as another means of payment have attracted the attention of financial and economic experts in recent times, but research on these means of payment and their relationship with economic and financial variables are scanty in Nigeria. This study, therefore, examined the nexus between the two key economic and financial variables (exchange rate and stock market price) and the most traded cryptocurrency (Bitcoin and Etherum) in Nigeria. The study used monthly data between August 2015 and December 2019 and employed the Generalized Autoregressive Conditional Heteroscedasticity (GARCH 1,1), Exponential Generalized Autoregressive Conditional Heteroscedasticity (EGARCH 1,1), and Granger causality technique to estimate the reaction of the volatility of exchange rates and stock market prices to volatility in cryptocurrency prices. The result shows that the stock market price is more influenced by the instability of bitcoin and ethereum prices than the exchange rate in Nigeria. Further, there is evidence of a one-way causality from bitcoin and ethereum to all share index. Given these findings, there is a need for the stock market investors in Nigeria to pay rapped attention to the movement of cryptocurrency prices.